FY2013-FY2015 Medium-Term Budget. (Policy Papers; Policy Paper ;, 2012)
The FY 13-15 Medium-Term Budget presented in this paper reflects the following main features: Unchanged administrative budget in real terms for FY 13. Overall spending (structural plus crisis/temporary) will be kept unchanged in real terms in FY 13 relative to the FY 12 budget (excluding the one-off additional cost of the 2012 Annual Meetings in Tokyo).Broadly unchanged administrative envelope in nominal terms for FY 13. This reflects the impact of the Executive Board's decision in March to grant no increase in the staff salary structure in the context of the 2012 Compensation Review. The 'structure increase' is the main component in the budget deflator applied to map the real total envelope into nominal terms. A capital budget dominated by the impact of the HQ1 Renewal Program. The final appropriation for this project, approved by the Executive Board in March 2011, is reflected in the proposed capital budget for FY 13.